The Real Manifestation of the Implementation of Chapter XIV of the 1945 Constitution Relating to The National Economy and Social Welfare in Order to Carry Out the Objectives of SDG's 2030 through the Mandiri Village Guided by the University - Huda, Khoiril (Universitas Negeri Semarang, 2018)
Universities or universities that should have carried out the Tri Dharma of Higher Education in a real manner. The Mandiri Village Fostered University (DMBU) has a concept that is very in accordance with various Semarang State University programs that have conservation jargons. This paper offers a variety of solutive steps so that activities related to conservation, student organizations and other activities in the campus environment can be in line with SDG's 2030. and 4, as well as articles 34 paragraph 2 and 3 which are the main points.